2017
DOI: 10.1159/000481626
|View full text |Cite
|
Sign up to set email alerts
|

Serum 1,5-Anhydroglucitol: Risk Factor of Acute Ischemic Stroke and Transient Ischemic Attack in Well-Controlled Diabetes

Abstract: Background: Serum 1,5-anhydroglucitol (1,5-AG) levels are a measure that provides information on daily glycemic variations. We evaluated whether 1,5-AG could be a possible marker of acute ischemic stroke (AIS) or transient ischemic attacks (TIA) in patients with diabetes mellitus (DM). Methods: We retrospectively reviewed electronic medical records of 5,294 AIS/TIA patients. Of the 5,294, 1,898 had diabetes and in 1,246, serum 1,5-AG levels were measured (group S). Group S was divided into 2 subgroups: hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It has been demonstrated confirmed that low serum 1.5-Ag levels may be a marker of acute ischemic stroke (AIS) or transient ischemic attack (TIA) risk in well-controlled diabetics (25). Nevertheless,studies have shown that 1,5-AG may be an important indicator not only for the evaluation of coronary heart disease and stroke (25)(26)(27)(28), but also for the assessment of nephropathy and retinopathy (29)(30)(31). There is evidence that 1,5-AG is a reliable glycemic marker for type 2 diabetes, even in patients with stages 1-3 chronic kidney disease (29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated confirmed that low serum 1.5-Ag levels may be a marker of acute ischemic stroke (AIS) or transient ischemic attack (TIA) risk in well-controlled diabetics (25). Nevertheless,studies have shown that 1,5-AG may be an important indicator not only for the evaluation of coronary heart disease and stroke (25)(26)(27)(28), but also for the assessment of nephropathy and retinopathy (29)(30)(31). There is evidence that 1,5-AG is a reliable glycemic marker for type 2 diabetes, even in patients with stages 1-3 chronic kidney disease (29).…”
Section: Discussionmentioning
confidence: 98%
“…Given that a large portion of the Chinese population suffers from elevated postprandial blood glucose alone but has normal fasting blood glucose, and the contribution of postprandial high blood glucose to cardiovascular disease is clear, the probability of developing cardiovascular and cerebrovascular diseases in diabetic patients with hypertension is significantly higher than that in patients with hypertension or diabetes alone. It has been demonstrated confirmed that low serum 1.5-Ag levels may be a marker of acute ischemic stroke (AIS) or transient ischemic attack (TIA) risk in well-controlled diabetics (25). Nevertheless,studies have shown that 1,5-AG may be an important indicator not only for the evaluation of coronary heart disease and stroke (25)(26)(27)(28), but also for the assessment of nephropathy and retinopathy (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, biomarkers have been sought to improve stroke prognosis and assessment. Despite their plethora, no convincing findings have yet established their use [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, low serum 1,5-anhydroglucitol (1,5-AG) levels have been shown to be a potential risk marker of stroke well-controlled DM [ 153 ].…”
Section: Emerging Biomarkersmentioning
confidence: 99%
“…They suggested that 1,5-AG is associated with stiffness but not with morphological changes of carotid arteries (27). Shiga demonstrated that a low serum 1,5-AG value (1,5-AG < 14 μg/mL) is a marker for acute ischemic stroke or transient ischemic attacks in patients with wellcontrolled DM (HbA1c < 7%) (29).…”
Section: Postprandial Hyperglycemia and Glucose Fluctuationmentioning
confidence: 99%